FOURNIER'S GANGRENE: MANAGEMENT EXPERIENCE OF 39 CASES - Ullah, Ikram; Ullah, Irfan; Iqbal, Qaisar; Saaiq, Muhammad (Journal of Postgraduate Medical Institute, 2017)
Objective: To determine the clinical presentation and management outcome of Fournier's gangrene. Methodology: This descriptive case series was carried out at the Department of Urology, Lady Reading Hospital, Peshawar over a 5-years period. All patients with Fournier's gangrene were included. The socio-demographic profile of the patients, area of involvement, underlying co-morbids, survival versus death, length of hospital stay and various surgical procedures undertaken were all recorded on a proforma. Results: Out of 39 patients, 89.74% (n=35) were males while 10.25% (n=4) were females. The age range was 17-63 years with a mean of 46.20 ±13.32 years. Poor general health/ malnutrition in 82.05% patients (n=32) was the commonest underlying cause. Scrotum (n=35; 89.74%) was the most frequently involved body area. The hospital stay was 7-63 days with a mean of 33.46 ±13.79 days. The interventions undertaken included serial radical debridements (n=39; 100%), split thickness skin grafts (n=19; 48.71%), direct closure of scrotal defects (n=9; 23.07%) and flaps (n=4; 10.25%). There were 07 mortalities (17.94% ). Conclusion: Fournier's gangrene causes significant morbidity, hospitalization and mortality in our population. Necrotizing fasciitis of the scrotum or perineum is the usual presentation. Aggressive resuscitation and surgical excision of the dead tissues followed by meticulous care of the surviving patient renders the resultant defects manageable with skin grafts and flaps.